For a community of the European educational research - Nuzzaci, Antonella (Revista Complutense de Educación, 2007)
The europeanization process of higher education system being implemented in the European Community countries continues to mobilize scholars and researchers creating new forms of scientific investment. It is a process that tries to create an out-and-out European Space for Higher Education, strictly coordinated with the national ones, able to link university, research, skill and production. The paper focuses on science of education field and problems regarding the capacity of action and coordination of the educational research at an international level. Some clarifications are delivered about strategical needs through which the various scientific communities may actively influence the creation of an European community for the pedagogical research.